201k views
1 vote
Pythagorean theorem

Pythagorean theorem-example-1

2 Answers

3 votes

Answer:

root of 45

Explanation:

User Shanky Singh
by
5.6k points
6 votes

Answer:

x = 3

x + 3 = 6

√45

Explanation:

the general theorem is

a^2 + b^2 = c^2

Givens

a = x

b = x + 3

c = √45

Solution

x^2 + (x + 3)^2 = (√45)^2 Substitute

x^2 + x^2 + 6x + 9 = 45 Expand the brackets. Square √45

2x^2 + 6x + 9 = 45 Subtract 45 from both sides

2x^2 + 6x - 36 = 0 Divide by 2

x^2 + 3x - 18 = 0 Factor

(x + 6)(x - 3) = 0 x+ 6 has no meaning in the real world.

x - 3 = 0

x = 3

Answer

a) 3

b) 6

c) √45

User Damageboy
by
5.0k points